2015
DOI: 10.1166/jnn.2015.10508
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated Multicellular Tumor Spheroids as a Tool to Test Novel Anticancer Nanosized Drug Delivery Systems <I>In Vitro</I>

Abstract: In the study, MCF-7 human breast adenocarcinoma cells were used to study cytotoxicity of novel anticancer nanosized formulations, such as docetaxel-loaded nanoemulsion and liposomal formulation of a lipophilic methotrexate (MTX) prodrug. In vitro study of cytotoxicity was carried out in 2 models, namely using 3D in vitro model based on multicellular tumor spheroids (MTS) and 2D monolayer culture. MTS were generated by tumor cell cultivation within alginate-oligochitosan microcapsules. In the case of the monola… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…This requires conducting studies using three-dimensional models that approximate the cellular and molecular composition of tumours. Researchers grow multicellular tumour spheroids , or MTS [178], seed porous scaffolds [179], and create miniature versions of various organs connected by vascular canals called ‘Chips’ [180]. Such models will help researchers develop therapies that act on tissues and systems and not just at the cellular and molecular levels.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…This requires conducting studies using three-dimensional models that approximate the cellular and molecular composition of tumours. Researchers grow multicellular tumour spheroids , or MTS [178], seed porous scaffolds [179], and create miniature versions of various organs connected by vascular canals called ‘Chips’ [180]. Such models will help researchers develop therapies that act on tissues and systems and not just at the cellular and molecular levels.…”
Section: Metastasis In Target Organsmentioning
confidence: 99%
“…They can also be used to generate organized cell arrangements in vitro according to the disease or tissue being studied, which is an advantage over 2D and several scaffold-free cell models [15]. Several natural (alginate [16], collagen [17], hyaluronic acid [18], basement membrane matrix [19]) and synthetic (poly(lactic acid-co-glycolic acid) [3], polycaprolactone [18], polyethylene glycol [20], polylactic acid [21]) polymer-based particles have been utilized to develop in vitro cancer models for various cancer studies.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have demonstrated that cells in microencapsulated spheroids were more resistant than those in monolayer culture against both free drugs 25 and nano-sized drug delivery systems, namely docetaxel-loaded nanoemulsions or methotrexate prodrug liposomal formulations. 26 In the current study, RI of the cells in the microencapsulated tumor spheroids against native DOX was found to be approx. 20-fold higher compared to that in the monolayer cell culture.…”
Section: Discussionmentioning
confidence: 56%